2020
DOI: 10.3390/toxins12050305
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mass Spectrometry to Determine the Diversity of Toxins Produced by Gambierdiscus and Fukuyoa Species from Balearic Islands and Crete (Mediterranean Sea) and the Canary Islands (Northeast Atlantic)

Abstract: Over the last decade, knowledge has significantly increased on the taxonomic identity and distribution of dinoflagellates of the genera Gambierdiscus and Fukuyoa. Additionally, a number of hitherto unknown bioactive metabolites have been described, while the role of these compounds in ciguatera poisoning (CP) remains to be clarified. Ciguatoxins and maitotoxins are very toxic compounds produced by these dinoflagellates and have been described since the 1980s. Ciguatoxins are generally described as the main con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…Blooms of these dinoflagellates have expanded worldwide reaching even European coasts. In fact, the presence of Gambierdiscus species and the related toxins and CFP intoxications have been repeatedly identified in Europe during the last decades, especially in the Canary Islands [1,2] and Madeira [3]. Besides ciguatoxins, which can cause long term neurological complications in humans as a consequence of their permanent activation voltage-gated sodium channels [4][5][6], the structure of an additional ciguatoxin-related toxin named 44-methylgambierone (MTX3) has been recently elucidated [7].…”
Section: Daily Oral Doses Of Ctx3c and Mtx3 For 28 Days Did Not Altered Enzyme Blood Levels Of Swiss Micementioning
confidence: 99%
“…Blooms of these dinoflagellates have expanded worldwide reaching even European coasts. In fact, the presence of Gambierdiscus species and the related toxins and CFP intoxications have been repeatedly identified in Europe during the last decades, especially in the Canary Islands [1,2] and Madeira [3]. Besides ciguatoxins, which can cause long term neurological complications in humans as a consequence of their permanent activation voltage-gated sodium channels [4][5][6], the structure of an additional ciguatoxin-related toxin named 44-methylgambierone (MTX3) has been recently elucidated [7].…”
Section: Daily Oral Doses Of Ctx3c and Mtx3 For 28 Days Did Not Altered Enzyme Blood Levels Of Swiss Micementioning
confidence: 99%
“…The structure of MTX-3 was recently suggested to be 44-methylgambierone [ 57 , 58 ], and has been detected in many Gambierdiscus and Fukuyoa species [ 59 , 60 , 61 , 62 , 63 , 64 ]. However, Murray et al [ 62 ] reported the toxicity (LD 50 ) of 44-methylgambierone injected intraperitoneally (i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…These factors include physical oceanographic properties (e.g., irradiance, wave power, depth, salinity, and temperature), biological (predation, direct and indirect disturbances), and anthropogenic drivers (habitat modification, pollution, and fishing practices) [ 10 , 15 , 98 , 99 , 100 , 101 , 102 , 103 ]. In culture, Gambierdiscus has displayed inter- and intra-species variability for growth, morphology, and quali-quantitative toxin profile [ 83 , 104 ], which can be influenced by capture location, culture parameters, and time spent in culture (phycological drift) [ 20 , 73 , 74 , 75 , 104 , 105 , 106 , 107 , 108 ]. Interactions between bacterial or other microbial co-inhabitants and Gambierdiscus indicated antagonism, competition, or benefits with impacts on fitness and bi-directional regulation in compound production [ 109 , 110 , 111 ].…”
Section: Introductionmentioning
confidence: 99%